2012
DOI: 10.1371/journal.ppat.1002781
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the ABO Blood-Group Dependence of Plasmodium falciparum Rosetting

Abstract: The ABO blood group influences susceptibility to severe Plasmodium falciparum malaria. Recent evidence indicates that the protective effect of group O operates by virtue of reduced rosetting of infected red blood cells (iRBCs) with uninfected RBCs. Rosetting is mediated by a subgroup of PfEMP1 adhesins, with RBC binding being assigned to the N-terminal DBL1α 1 domain. Here, we identify the ABO blood group as the main receptor for VarO rosetting, with a marked prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 70 publications
(125 reference statements)
4
111
1
1
Order By: Relevance
“…These changes were associated with significant Odds ratios suggesting decreased and increased risks of eBL among individuals with O and non-O blood groups respectively. These findings are interpreted to be a reflection of decreased and increased risks of severe malaria in individuals with O and non-O blood groups respectively as previously reported in earlier studies [3,4,12,13]. Previous studies have shown that malaria was associated with immune suppression, increased EBV load and polyclonal B cell activation, all of which are important in the pathogenesis of eBL [1,7].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These changes were associated with significant Odds ratios suggesting decreased and increased risks of eBL among individuals with O and non-O blood groups respectively. These findings are interpreted to be a reflection of decreased and increased risks of severe malaria in individuals with O and non-O blood groups respectively as previously reported in earlier studies [3,4,12,13]. Previous studies have shown that malaria was associated with immune suppression, increased EBV load and polyclonal B cell activation, all of which are important in the pathogenesis of eBL [1,7].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that malaria was associated with immune suppression, increased EBV load and polyclonal B cell activation, all of which are important in the pathogenesis of eBL [1,7]. These malaria induced immune deregulations would be greater in persons with non-O blood groups because of their vulnerability to severe malaria [3,4,12,13]. Conversely, persons with O blood group, which is associated with non-severe malaria, would incur milder malaria associated pathology because of their reduced vulnerability to severe malaria [3,4,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…This is because one of the ligands associated with rosette formation in P falciparum (P falciparum erythrocyte membrane protein 1 [PfEMP1]) has no orthologs in P vivax. Thus, all of the receptors on the host red cell corresponding to PfEMP1, such as complement receptor 1 (CD35), 27 blood group antigens (A and B), [28][29][30] heparan sulfate, 31 and thrombospondin (CD36), 32,33 may not be relevant to P vivax rosette formation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the structure of the N‐terminal DBL1‐CIDR1 didomain of var0, the CIDR domain forms a compact α‐helical bundle. This packs tightly against the DBL domain through an additional region containing a four‐stranded anti‐parallel β‐sheet 41. Whether different CIDR domains adopt different architectures, or whether truncation of the MC179 CIDR domain or the crystallization conditions have caused this structure to spread apart, remains to be seen and will require the determination of more CIDR structures, alone and in complex with their ligands.…”
Section: Introductionmentioning
confidence: 99%